2023
DOI: 10.1002/ncp.11087
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes associated with blenderized tube feedings in adults: A systematic review

Erin R. Schultz,
Yeonsoo Kim

Abstract: Nearly half a million individuals in the United States are dependent on enteral nutrition to meet their nutrition needs. Public interest in blenderized tube feeding (BTF) has increased over the past decade; however, medical professionals indicate a lack of knowledge about these products and their effects. The purpose of this review is to analyze clinical outcomes in adults who use a BTF formula as their primary nutrition source. A literature search was conducted in PubMed, Scopus, and CINAHL using search terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…10,[13][14][15] There are a lack of randomized controlled trials comparing CEFs with BTFs; however, observational studies indicate BTFs are associated with improved health outcomes and quality of life, such as decreased hospital use and increased patient satisfaction compared with CEFs. 3,16,17 More recent studies have shown that BTFs are safe and well tolerated. [18][19][20] Barriers to BTF use include the need for a specialized blender, time and labor involved in preparing BTFs, cost, difficulty managing BTFs away from home, concerns caused by commercial insurance coverage, and inadequate support from the family or HCP.…”
Section: Btf Benefits and Barriersmentioning
confidence: 99%
“…10,[13][14][15] There are a lack of randomized controlled trials comparing CEFs with BTFs; however, observational studies indicate BTFs are associated with improved health outcomes and quality of life, such as decreased hospital use and increased patient satisfaction compared with CEFs. 3,16,17 More recent studies have shown that BTFs are safe and well tolerated. [18][19][20] Barriers to BTF use include the need for a specialized blender, time and labor involved in preparing BTFs, cost, difficulty managing BTFs away from home, concerns caused by commercial insurance coverage, and inadequate support from the family or HCP.…”
Section: Btf Benefits and Barriersmentioning
confidence: 99%